Controlled trial comparing olsalazine and sulphasalazine for maintenance treatment of ulcerative colitis. - Jewell, D; Ireland, A (Informa Healthcare, 1988)
Olsalazine and sulphasalazine were compared in a double-blind, double-dummy trial in the prevention of relapse of ulcerative colitis over 6 months. The majority were taking sulphasalazine. They were randomized to receive either olsalazine, 500 mg b.d., or sulphasalazine, 1 g b.d. Of 82 patients, 16 relapsed on olsalazine compared with 10 of 82 on sulphasalazine. This difference was not statistically significant (p = 0.16). Twenty-one patients reported adverse events in the olsalazine group, of whom 16 were withdrawn, while 20 patients reported adverse events in the sulphasalazine group, with 9 of them being withdrawn. The differences were not statistically significant. No major haematological or biochemical abnormalities occurred. Thus, olsalazine is similar to sulphasalazine for the prevention of relapse of ulcerative colitis.